Platform Penjualan Kerajinan Kulit di Saung Kulit Garut - Hanhan Hanafiah Solihin; Miftah Fauzi; Herna Gunawan (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2025)
Saung Kulit Garut Store is a Small and Medium Enterprises (SMEs) company which is experiencing problems in its marketing sector, where the company only uses WhatsApp media from contact to contact to order products and services for sales promotion which is not optimal. Creating an online sales platform is the solution to this problem. This system was created using the Rapid Application Development (RAD) method. This platform has two main functions. First, for customer users, every visitor to the platform can view the product catalog, use the platform services, and can order products according to the customer's wishes. Second, the admin can manage product data, customer data, manage orders and obtain reports.